(untitled) (Journal of Asian Development Studies, 2023)
Food security is an essential concern of developing countries, primarily in rural areas. To achieve food security, it is vital to explore its determinants not only empirically but also review important studies to be undertaken to highlight the gaps left in the empirical research. Seeking this, the present systematic review and meta-analysis were accomplished to assess the determinants of food security in the rural households of developing countries. The three themes or components of food security, i.e., food availability, accessibility of food, and utilization of food, have been covered in the literature. The most studied component of food security was food availability, followed by food accessibility, while food utilization was the least studied component. The study recommends replicating such studies, and future research must be geared toward food utilization.